Construção de marca em redes sociais: interações no site Flickr e seus desdobramentos identitários - Wajnsztejn, Marina (2010)
The identities pathways traversed digitally and bodily by Flickr website users are vital for the functioning of the community, our study object. In order to analyze the website s identity, we start by conceptualizing the Flickr brand into two domains: digital and physical. In the digital field, the user participation is done contractually, with Flickr as the manipulative sender, moderator sender and judge sender. In the physical event, Flickr s role is evident to the user as a celebration, in which the recipient is invited to interact with other users in a physical realm that strengthens the community ties. This project is based on the theory and methodology of generative semiotics by A.J. Greimas, as well as on the developments provided by E. Landowski, particularly the concepts of contract, simulacrum, interaction and meaning production, and on the plastic semiotics by J.-M. Floch. We analyzed the sender s modes of presence and how it acts upon the recipients, comparing the simulacrum with visibilities that allow themselves to be seen. The photographic distribution process, in its turn, was considered under V. Flusser s concept of the human-machine and, due to its digital character, human-machine-interface. Using this construct, we studied the modes of acknowledgement through which the agent builds the site´s identity using photographs of his body present in the event. We identify how the ventures dynamic between the digital and the physical world correspond to the survival and strengthening of Flickr that brought us to the development of a results typology about the meaning effects of advertising practices considered innovative in the contemporary aesthetic